Propuesta de mejora del proceso productivo para la elaboración de pasta de cacao (theobroma cacao), en la empresa Aroma Ecuador S.A. - Ortiz Lozovaya, Alicia Margarita (2020)
The present paper was based on a proposal to improve the production line of cocoa paste in the company Aroma Ecuador SA. Through an initial checklist, the current situation of the organization was known, resulting in 85 percent of non-conforming criteria, concluding that the organization does not handle tools for improvement. For this reason, the objective of this study was to make improvements in the operation times in the cocoa bean milling process with the application of Lean Six Sigma, the same that uses the DMAIC methodology as an improvement tool. This tool proposes the improvement of processes in 5 phases: define, measure, analyze, improve and control; same, that identify opportunities in a process, characterize it, perfect it and finally control the proposed improvements. As a result of DMAIC, it was verified that the bottlenecks are located in the milling process, where it was evidenced that there is a lack of cleanliness, delaying the production time. By using statistical tools, it was found that there were differences when implementing the improvement. For this, 8 repetitions were taken at random by each mill (A and B), before implementing the improvement; where, there were no significant differences between the times registered, by means of an analysis of variance. Subsequently, the improvement was implemented only in mill A, to evaluate the results, versus mill B, where significant differences between the recorded times were evident. Finally, a cost/benefit analysis was carried out, equivalent to $2.27, with an IRR of 24 percent, the NPV obtained corresponds to $20,507.86 and the break-even point in income is equivalent to $ 295.53.